(untitled) (Research, Society and Development, 2021)
The present work had as objective the elaboration of banana peel flour (Musa spp.) bleached by convective drying and determine the physicochemical parameters and bioactive compounds. The peels were washed, sanitized with sodium hypochlorite solution and bleached. Then they were dried in an oven with air circulation at 60ºC and ground. Soon after, the flour was evaluated for physicochemical parameters: pH, total soluble solids (°Brix), TSS/ATT ratio, total titratable acidity, water content, ash, total solids and bioactive compounds: total tannins (TT) and total phenolic compounds (CFT). The flour had a pH of 6.30, higher than the in natura peel 5.53, the brix of 15.3 and that of the peel 6.50 °Brix, the water content 8.24 (b.u) and of the peel 86.2 (b.u). The CFT found in the flour was 124.48 mg EAG/100g, which was higher than that found in the in natura sample, 69.44 mg EAG/100g. The TT values obtained in the flour were 112.900 mg EAT/100g lower than in the peel, 394.900 mg EAT/100g. The water content of the banana peel flour is within the limits established by ANVISA and can therefore be stored at room temperature without risk of microorganism development. The results obtained with respect to bioactive compounds indicate that the banana peel flour contains significant values and can be incorporated into the human diet.